Pressing the fight : print, propaganda, and the Cold War - Turner, Catherine, 1968-; Barnhisel, Greg, 1969- (Book collections on Project MUSE., 2010)
"In this volume, scholars from a variety of disciplines explore the myriad ways print was used in the Cold War. Looking at materials ranging from textbooks and cookbooks to art catalogs, newspaper comics, and travel guides, they analyze not only the content of printed matter but also the material circumstances of its production, the people and institutions that disseminated it, and the audiences that consumed it. Among topics discussed are the infiltration of book publishing by propagandists East and West; the distribution of pro-American printed matter in postwar Japan through libraries, schools, and consulates; and the collaboration of foundations, academia, and the government in the promotion of high culture as evidence of superiority of Western values"--Fly leaf.